Co‐producing research in the "Red Zone": Adaptation to fieldwork constraints with a transdisciplinary approach. Issue 4 (2nd August 2018) - Laborde, Sarah; Phang, Sui Chian; Ahmadou, Mouadjamou; Henry, Nathaniel; Fernández, Alfonso; Durand, Michael; Hamilton, Ian M.; Kari, Saïdou; Mahamat, Aboukar; Mark, Bryan; Scholte, Paul; Shastry, Apoorva; et al.
Abstract : Fieldwork rarely goes to plan. In geography, anthropology, earth sciences and other research activities that rely on field data, trade‐offs are required between planning and execution. This article addresses the adaptation of research projects to changing fieldwork conditions. It is based on a case study of interdisciplinary and international "Coupled Human and Natural Systems" research situated in the Far North of Cameroon. The research project underwent drastic changes because of escalating insecurity in the field site, caused by Boko Haram, a terrorist group active in north‐east Nigeria and neighbouring regions. We use network analysis to show that our research team became larger, more connected and less clustered to accommodate for the changes in fieldwork accessibility. This process of adaptation led our research team towards tighter interdisciplinary collaboration, the co‐production of research between academic scientists with little or no local field experience and non‐academic practitioners with field knowledge, and a better dissemination of research outcomes through stronger partnerships with local organisations – overall, an increasingly transdisciplinary research pathway. Based on this case study, we discuss features of adaptive research projects facing high‐uncertainty field conditions, which is an increasingly relevant issue for many researchers, for example those working in parts of the Sahel or Middle East. Abstract : This article addresses the adaptation of research projects to changing fieldwork conditions, based on a case study of interdisciplinary and international "Coupled Human and Natural Systems" research situated in the Far North of Cameroon. We use network analysis to show that our research team became larger, more connected and less clustered to accommodate for growing insecurity in the field. This process of adaptation led our research team towards the co‐production of research between academic scientists with little or no local field experience and non‐academic practitioners with field knowledge – an increasingly transdisciplinary research pathway.